Kedudukan Hukum Akta Penegasan Notaris Terhadap Akta Perubahan Perseroan Terbatas Yang Tidak Didaftarkan - Julianty, Vivy; Mekka Putra, Mohamad Fajri (Universitas Semarang, 2022)
This study aims to analyze the legal standing of the deed of amendment to the general meeting of shareholders of a limited liability company and the legal liability of a notary whose deed of amendment to the company is not registered. A notary is a public official who is authorized to make an authentic deed, in making a deed of establishment and changes to a limited liability company, the parties want to be protected and get legal certainty. This writing has urgency, namely whether or not the deed made by a Notary has been requested to change the deed to the Ministry of Law and Human Rights so that it cannot be approved by the Ministry of Law and Human Rights. This research method uses normative juridical research methods. This research has a new perspective because it analyzes the legal position of the deed of amendment to the general meeting of shareholders of a limited liability company that is not registered with the Ministry of Law and Human Rights. The results of the study show that the Notary is responsible for compensating for losses by making a deed of the amendment, changing and correcting the registration data of a limited liability company when there is an error in data entry. The responsibility of a notary for a deed of change of a limited liability company that is not registered is that a notary can make a deed of confirmation or a deed of confirmation of the deed that is not requested, this is done if the shareholders feel they are not harmed due to negligence committed by the board of directors and carry out an inauguration or a deed of confirmation can be made and requested again. Tujuan dari penelitian ini adalah untuk menganalisis kedudukan hukum akta, perubahan rapat umum pemegang saham perseroan terbatas dan tanggung jawab hukum Notaris yang akta perubahan perseroan tidak terdaftar. Notaris adalah pejabat umum yang berwenang dalam membuat akta autentik, pada proses pembuatan akta pendirian dan perubahan perseroan terbatas para penghadap ingin terlindungi dan mendapatkan kepastian hukum. Penulisan ini memiliki urgensi yaitu keabsahan tidaknya akta yang dibuat Notaris tetapi tidak dimohonkan perubahan akta kepada Kementerian Hukum dan HAM sehingga tidak dapat persetujuan oleh Kementerian Hukum dan HAM. Metode penelitian ini menggunakan metode penelitian yuridis normatif. Penelitian ini mempunyai kebaruan pandangan sebab menganalisis kedudukan hukum akta perubahan rapat umum pemegang saham perseroan terbatas yang tidak didaftarkan ke Kementerian Hukum dan HAM. Hasil penelitian menunjukan bahwa Notaris bertanggung jawab untuk mengganti kerugian melalui pembuatan akta perubahan, mengganti serta melakukan perbaikan pendaftaran perseroan terbatas jika terjadi kesalahan dalam penginputan data. Tanggung jawab Notaris atas akta perubahan Perseroan yang tidak didaftarkan ialah Notaris dapat membuat akta pengukuhan ataupun akta penegasan terhadap akta yang tidak dimohonkan, hal tersebut dilaksanakan jika pemegang saham merasa tidak dirugikan akibat kelalaian yang dilakukan pihak direksi dan melakukan pengesahan atau akta penegasan yang dapat diolah dan dipermohonkan kembali.